Residual Benign Prostate Glandular Tissue after Radical Prostatectomy is Not Associated with the Development of Detectable Postoperative Serum Prostate Specific Antigen. Issue 3 (27th September 2021) - Greenberg, Scott A.; Washington, Samuel L.; Lonergan, Peter E.; Cowan, Janet E.; Baskin, Avi S.; Nguyen, Hao G.; Odisho, Anobel Y.; Simko, Jeffry P.; Carroll, Peter R.
Abstract : Abstract : Purpose: To determine if benign glandular tissue at the surgical margin (BGM) is associated with detectable prostate specific antigen (PSA) and/or biochemical recurrence (BCR) after radical prostatectomy (RP). Materials and Methods: Participants underwent RP for localized prostate cancer between 2004 and 2018. Regression analysis was used to identify demographic, clinical and surgical factors associated with the likelihood of BGM presence on surgical pathology. Oncologic outcomes included detectable PSA (>0.03 ng/ml), BCR (≥0.2 ng/ml) and progression to BCR or salvage treatment after detectable PSA. Life tables and Cox proportional hazards regression models were used to determine the association of BGM and risk of oncologic outcomes. Results: A total of 1, 082 men underwent RP for localized prostate cancer with BGM reported on surgical pathology and an undetectable postoperative PSA. BGM was present on 249 (23%) specimens. Younger age, bilateral nerve sparing surgery and robotic approach were associated with presence of BGM while malignancy at the surgical margin (MSM) was not. At 7 years after RP, 29% experienced detectable PSA and 11% had BCR. In the subgroup of men who reached detectable PSA, 79% had progression within 7 years. On multivariate Cox proportional hazards regression, BGM status was not independently associated with detectable PSA, BCR and/or progression from detectable PSA to BCR or salvage treatment. Conclusions: The presence of BGM at RP was not associated with increased risk of MSM, detectable PSA, BCR or progression after detectable PSA.